Enhancing cycling as an alternative urban mobility in small 15 km radius cities in low-income countries: a case study of Lusaka and Livingstone cities - Chishiba, Orleans Mwenya (Stellenbosch : Stellenbosch University, 2025)
Chishiba, O. M. 2025. Enhancing cycling as an alternative urban mobility in small 15 km radius cities in Low-Income Countries: A Case Study of Lusaka and Livingstone Cities. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/61c17342-6012-4485-bc3c-f079ab7a70b6